2018
DOI: 10.15252/embr.201745241
|View full text |Cite|
|
Sign up to set email alerts
|

Mitofusin gain and loss of function drive pathogenesis in Drosophila models of CMT 2A neuropathy

Abstract: Charcot-Marie-Tooth disease type 2A (CMT2A) is caused by dominant alleles of the mitochondrial pro-fusion factor Mitofusin 2 (MFN2). To address the consequences of these mutations on mitofusin activity and neuronal function, we generate models expressing in neurons the two most frequent substitutions (R94Q and R364W, the latter never studied before) and two others localizing to similar domains (T105M and L76P). All alleles trigger locomotor deficits associated with mitochondrial depletion at neuromuscular junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 75 publications
(171 reference statements)
7
58
0
1
Order By: Relevance
“…Zooms of the mitochondrial network in Miro1 CKO cell bodies revealed large mitochondrial units of accumulated and hyperfused "giant" mitochondria ( Fig 6C), which were further resolved using high resolution imaging (Airyscan -Zeiss), a method that increases imaging resolution by a factor of 1.7 ( Fig S4). Giant mitochondria have been identified in a number of models where either mitochondrial fission / fusion proteins or mitophagy has been altered (Chen et al, 2007;El Fissi et al, 2018;Kageyama et al, 2014;Kageyama et al, 2012;Yamada et al, 2018a;Yamada et al, 2018b). Interestingly, we observed that a proportion of Miro1 CKO cells presenting giant mitochondria showed an accumulation of ubiquitin surrounding the aberrant mitochondrial particles similar to what happens during ageing or Lewy Body Disease ( Fig 6D) .…”
Section: Loss Of Miro1 In Principal Neurons Induces the Appearance Ofmentioning
confidence: 52%
See 1 more Smart Citation
“…Zooms of the mitochondrial network in Miro1 CKO cell bodies revealed large mitochondrial units of accumulated and hyperfused "giant" mitochondria ( Fig 6C), which were further resolved using high resolution imaging (Airyscan -Zeiss), a method that increases imaging resolution by a factor of 1.7 ( Fig S4). Giant mitochondria have been identified in a number of models where either mitochondrial fission / fusion proteins or mitophagy has been altered (Chen et al, 2007;El Fissi et al, 2018;Kageyama et al, 2014;Kageyama et al, 2012;Yamada et al, 2018a;Yamada et al, 2018b). Interestingly, we observed that a proportion of Miro1 CKO cells presenting giant mitochondria showed an accumulation of ubiquitin surrounding the aberrant mitochondrial particles similar to what happens during ageing or Lewy Body Disease ( Fig 6D) .…”
Section: Loss Of Miro1 In Principal Neurons Induces the Appearance Ofmentioning
confidence: 52%
“…Though VDAC1 is a substrate for Parkin it is dispensable for the mitophagic loss of mitochondria (Narendra et al, 2010) which may therefore, explain the disparity in the changes of different Parkin substrates in the Miro1 CKO mice. Upregulation of the mitochondrial fusion machinery and in particular gain of function mutations of Mfn2 associated with Charcot Marie Tooth-2 (CMT2) pathology are linked to mitochondrial remodelling and the accumulation of hyperfused giant mitochondria in the neuronal somas (El Fissi et al, 2018;Santel and Fuller, 2001). To facilitate determining the impact of Mfn upregulation in vivo we generated a new mouse line where mitoDendra is expressed solely in neurons expressing CamKIIα-Cre driven Miro1 recombination allowing identification of Miro1 deleted neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of EMBO Reports, El Fissi et al established a fly model to analyze CMT2A pathogenesis in vivo [1]. Marf is the ubiquitously expressed fly homolog of mitofusin.…”
Section: Embo Reports (2018) 19: E46502mentioning
confidence: 99%
“…In this issue of EMBO Reports, El Fissi et al established a fly model to analyze the consequence of frequently occurring MFN2 mutations on locomotor behavior, mitochondrial morphology, and function and find that some pathogenic mutants enhance fusion activity, indicating that increased mitochondrial fusion can drive CMT2A-like pathology [1]. A disruption of these processes can cause severe neurodegeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation